TRANSFORMASI BIROKRASI PEMERINTAH : PERGESERAN PARADIGMA DARI ERA KLASIK KE MODERN DALAM PENERAPAN GOOD GOVERNMENT DI ERA DIGITAL - Silitonga, Anest Juliana (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This study aims to examine the transformation of government bureaucracy from the classical paradigm to the modern paradigm. The classical model, characterized by rigid hierarchy, procedural orientation, and centralization, is gradually shifting toward a modern bureaucracy that emphasizes efficiency, responsiveness, and the use of digital technology. Using a descriptive qualitative approach and literature review method, this research analyzes various scholarly sources, public administration theories, and relevant policy documents. The findings reveal that this transformation is driven by increasing public demands, globalization, and technological innovation. The paradigm shift not only affects the structure and processes of bureaucracy but also necessitates changes in work culture and the mindset of public servants. This study recommends the importance of continuous bureaucratic reform to achieve adaptive, accountable, and service-oriented governance.